Market knowledge and new product performance: the mediating effects of new product creativity - Dabrowski, Dariusz (Journal of Business Economics and Management, 2019)
Market knowledge is recognised as an important predictor of new product performance, which existing studies have proven. However, a missing link in this relationship is creativity, and specifically, as a natural process in product innovation. This study aims to examine a model that includes two mediating mechanisms between market knowledge scope and two new product outcomes, respectively: a new product’s competitive advantage and its commercial success. In both cases two mediators are used that represent dimensions of creativity—i.e. a product’s meaningfulness and novelty. The model was tested on a sample of 374 Polish medium-high- and high-technology companies using structural equation modelling. The results indicated that market knowledge is transferred to both new product outcomes through new product creativity, albeit somewhat differently. The first mediating mechanism, which explains the factor of competitive advantage, operates only through the indirect effects of both the product’s meaningfulness and its novelty. The second mechanism works directly, through the market knowledge’s effect on commercial success, as well as indirectly, through product meaningfulness. Subsequently, theoretical and managerial implications as well as indications for future research are provided based on these findings.